THE INFLUENCE OF LEARNING STYLES AND SCHOOL FACILITIES ON STUDENT LEARNING OUTCOMES IN CREATIVE PRODUCT AND ENTREPRENEURSHIP SUBJECTS IN NORTH JAKARTA PUBLIC HIGH SCHOOLS - Debora, Tiurma; Sumiati, Ati; Wahono, Puji (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to evaluate the extent to which students' learning styles affect their learning outcomes at SMK Negeri North Jakarta, identify variations in students' learning styles and their relationship with learning outcomes, and assess the influence of school facilities on the quality of the learning process. In addition, this study also looks at whether or not there is an influence of students' learning styles individually or together with school facilities on learning outcomes. This study uses a quantitative approach with primary data in the form of learning styles and school facilities, and secondary data in the form of learning outcomes. Data were collected through distributing questionnaires and collecting daily test scores at vocational schools that have office management majors in North Jakarta. The study population involved 212 students from six classes in three schools, with a sample of 195 students selected through proportional sampling method. Data analysis was conducted using Partial Least Square (PLS) technique. The results showed that learning styles have a significant positive effect on learning outcomes in entrepreneurial creative product subjects. The more appropriate the application of learning styles, the better the learning outcomes achieved. School facilities are also proven to have a positive effect on learning outcomes. Thus, schools have an important role in improving facilities and understanding variations in student learning styles.